2008
DOI: 10.1016/j.yhbeh.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Opposing actions of 5HT1A and 5HT2-like serotonin receptors on modulations of the electric signal waveform in the electric fish Brachyhypopomus pinnicaudatus

Abstract: Serotonin (5-HT) is an indirect modulator of the electric organ discharge (EOD) in the weakly electric gymnotiform fish, Brachyhypopomus pinnicaudatus. Injections of 5-HT enhance EOD waveform "masculinity", increasing both waveform amplitude and the duration of the second phase. This study investigated the pharmacological identity of 5-HT receptors that regulate the electric waveform and their effects on EOD amplitude and duration. We present evidence that two sets of serotonin receptors modulate the EOD in op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 60 publications
4
28
0
Order By: Relevance
“…Our data suggest an important excitatory function for AVT in both species (even stronger in G. omarorum, as discussed above), but provide no evidence that 5-HT modulates EOD rate. Previous studies in both species evaluating the effects of the activation of the 5-HT system on locomotor and electric behaviors did not report 5-HT actions on EOD rate in Brachyhypopomus (Allee et al, 2008), whereas pharmacologically increased levels of 5-HT evoked a decrease in EOD rate in Gymnotus (Capurro et al, 1997).…”
Section: Conclusion and Speculationsmentioning
confidence: 73%
See 2 more Smart Citations
“…Our data suggest an important excitatory function for AVT in both species (even stronger in G. omarorum, as discussed above), but provide no evidence that 5-HT modulates EOD rate. Previous studies in both species evaluating the effects of the activation of the 5-HT system on locomotor and electric behaviors did not report 5-HT actions on EOD rate in Brachyhypopomus (Allee et al, 2008), whereas pharmacologically increased levels of 5-HT evoked a decrease in EOD rate in Gymnotus (Capurro et al, 1997).…”
Section: Conclusion and Speculationsmentioning
confidence: 73%
“…Pharmacological stimulation of the 5HT 1A receptors in B. gauderio did not affect contest outcome (seven out of eight injected residents won the contest), aggression levels or motivation towards combat (Fig.3). Previous reports in B. gauderio showed that 8-OH-DPAT diminishes amplitude and duration of the EOD waveform (Allee et al, 2008), which is an important proxy of male body size and endocrine status (Gavassa et al, 2011). The lack of effect of the 5-HT 1A agonist in B. gauderio is relevant because this is the first species in which the administration of 5-HT 1A receptor agonists (A)Behavioral protocol: dyads of G. omarorum (0-50% weight asymmetry, N=33) were placed in equal-sized compartments separated by a glass gate that was removed 10min after sunset.…”
Section: Differential Serotonergic Modulation Of Two Types Of Aggressionmentioning
confidence: 85%
See 1 more Smart Citation
“…Earlier behavioural studies have shown that systemic application of 5-HT decreases aggressive behaviours in weakly electric fish and affects the waveform of the EOD in certain species (Maler and Ellis, 1987;Allee et al, 2008;Smith and Combs, 2008;Stoddard et al, 2006), but we do not yet know under which conditions intrinsic 5-…”
Section: Discussionmentioning
confidence: 93%
“…The hormonal drivers of EOD plasticity have been identified as androgen driving long-term changes , and peptide hormones driving mid-term changes, with serotonin acting centrally Allee et al, 2008) and melanocortins acting directly on the electrocyte ). However, a prior lab study failed to correlate endogenous circulating androgen levels and EOD parameters ).…”
Section: Discussionmentioning
confidence: 99%